Productivity and quality of bagging fruit of hybrid tomatoes (Bioscience Journal, 2020)
Tomato cultivation is challenging due to the high susceptibility to various pests and diseases. Fruit borer insects make fruits unfeasible for commercialization because this favors colonization by pathogens. The loss due to borers can be avoided by bagging the bunches of fruit, helping the conventional crop to be more sustainable, reduce the use of pesticides, reduce the residue in fruits and improve the quality of life of rural workers, by less exposure to agrochemicals and poisoning problems. The results are products of better quality and with the possibility of better profitability. The objective of this study was to evaluate the efficiency of tomato bagging in the control of fruit borer insects, and its effects on lycopene content, taste, productivity and profitability. The experiment was conducted in a field in the municipality of Uberaba-MG, from November 2016 to September 2017. The experimental design was a randomized block design, in a 3 x 5 factorial, with four replications. The factors consisted of three tomato hybrids: Dominador (salad), Ravena (Italian) and Carina Star (Santa Cruz), and fruit bagging types, made by TNW (tissue-non-woven), tulle, organza, brown craft and a control, without fruit bagging. The decision of bagging use depends on the pest incidence in the area and the change in the agronomic characteristics of the tomato. The organza and tulle fruits bagging reduce the incidence of borer insects, relative to the control, in the cultivation in spring-summer. The Dominador presents higher brix content among the evaluated hybrids. Carina Star, when bagged with organza, produces fruits with higher levels of lycopene, and is 116% superior to the other cultivars. From the second harvest, organza fabric is the most profitable bagging, since it is the only one that can be reused several times and is therefore more sustainable.